A broadband vibration energy harvesting model for multiple cantilever beams - Thong, Li Wah; Kok, Swee Leong; Roszaidi, Ramlan (2014)
Conventional vibration energy harvesters are required to function only on sole resonant frequency and to harvest energy on a restricted bandwidth. In this paper, a novel mathematical model of a energy harvester is proposed to confront the problem and to harvest energy in a broader spectrum of frequency. Simulation results show that the proposed model is able to generate broadband energy with suitable optimized parameters. Furthermore, it is observed that by reducing the frequency ratio between cantilever beams, the ripples effect in the energy bandwidth can be reduced.